Policies to build research infrastructures in Europe: Following traditions or building new momentum? - Thomas Stahlecker; Henning Kroll (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2013)
As next to all aspects of research are becoming internationalised at a more and more rapid pace the need for the creation of transnational research infrastructures can no longer be seen as limited to certain fields of natural sciences. Against the background, new policies have been launched with the stated ambition of developing world-class research infrastructures through the creation of critical mass for scientific undertakings across the continent. Thus they seek to contribute to the establishment of a European Research Area in which the fragmentation of scientific resources can be minimised. Against this background, it was the aim of this paper to analyse whether selected policies with the aim to build capacity in this field are likely to contribute to their objective to help foster the emerging European Research Area. Based on a recent representative survey of 598 European research organisations and available data for the 6th and 7th Framework Programmes for Research, evidence was collected to address two main research questions. Firstly, we found that the four largest EU countries (Germany, France, Italy, UK) still dominate both lines of actions aimed at building or extending research infrastructures in Europe (I3 actions and design actions) with a view to budget, project co-ordination and, to a lesser degree, participation. Nonetheless, their dominance seems to subside gradually. In different respects, some smaller Member States have become better integrated in funding schemes of the 7th Framework Programme than they were under the 6th Framework Programme. Beneficiaries in that sense include Denmark, Finland, Norway and Greece. On the one hand, our findings thus illustrate that the aim to overcome fragmentation is clearly reflected in structure of the policy programmes while, on the other hand, they illustrate that a challenging task remains ahead. Secondly, we found that the structure of expenditure and participation in the related actions under both the 6th and the 7th Framework Programme does not yet match well with the factual pattern of research infrastructures in Europe. Partially, that is due to the European Framework Programme's traditional focus on (nuclear) physics and astronomy that continues to take the largest share of all related allocations of funding. Additionally, however, there is evidence of conscious priority setting in new fields such as energy research and life sciences. Finally, the structure of allocations and participation under the 7th Framework Programme has come to reflect the factual pattern of research infrastructures in Europe better than was the case under FP 6, not least due to in increased acknowledgement of the role of the social sciences. In conclusion, the European effort to build and strengthen key research infrastructures seems well on track to build new momentum although it is unlikely to overcome the persistent disparities across the continent in the nearer future.
urn:nbn:de:0011-n-2347646
Keywords: 330